Regulation of podocyte injury by CircHIPK3/FUS complex in diabetic kidney disease - Liu, Feng; Huang, Jing; Zhang, Chunyun; Xie, Yaru; Cao, Yiling; Tao, Li; Tang, Hui; Lin, Jihong; Hammes, Hans-Peter; Huang, Kun; Yi, Fan; Su, Hua; et al. (International journal of biological sciences, 2022)
Diabetic kidney disease (DKD) is a major microvascular complication of diabetes mellitus and is one of the leading causes of end-stage kidney disease. Circular RNAs (circRNAs) are a class of endogenous non-coding RNAs that play important roles in various diseases, yet their roles in DKD are poorly understood. CircRNA HIPK3 (circHIPK3), a highly conserved circRNA, is closely related to various cellular functions, including cell proliferation and apoptosis. The association between circHIPK3 and diabetic complications has been well demonstrated in multiple previous studies. However, the role of circHIPK3 in podocyte injury in DKD remains unclear. Herein, we discovered that circHIPK3 expression is markedly elevated in cultured podocytes under high-glucose (HG) conditions and glomeruli of diabetic mice, which is closely associated with podocyte injury in DKD. Functionally, lentivirus-mediated knockdown of circHIPK3 dramatically suppresses HG-induced podocyte apoptosis in vitro. Therapeutically, silencing circHIPK3 by adeno-associated virus-mediated RNA interference ameliorates podocyte injury and albuminuria in STZ-induced diabetic mice. Mechanistically, circHIPK3 facilitates the enrichment of fused in sarcoma (FUS) on the ectodysplasin A2 receptor (EDA2R) promoter, resulting in the upregulation of EDA2R expression and activation of apoptotic signaling. Taken together, these results indicate circHIPK3/FUS/EDA2R axis as a therapeutic target for podocyte injury and DKD progression.